BASRAH SEBAGAI LABORATORIUM HADIS AWAL: KONSTRUKSI SANAD DAN KRITIK PERIWAYATAN - Fachrul Rozy (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
This study examines the construction of ḥadīth scholarship in the region of Basrah as one of the major centers for the development of ḥadīth sciences in Islamic history. Founded during the caliphate of ʿUmar ibn al-Khaṭṭāb, Basrah rapidly evolved into a significant intellectual, political, and social hub that produced numerous Companions, Successors (tābiʿun), and Followers of the Successors (tābiʿ al-tābiʿīn) as transmitters of ḥadīth. The scholarly tradition of Basrah was characterized by a distinctive methodology of ḥadīth criticism, particularly its strong emphasis on isnād analysis, the use of textual and linguistic approaches, and a selective attitude toward the validity of transmission. Sociopolitical dynamics, including the emergence of various theological and legal trends as well as the practice of tadlīs, significantly influenced the patterns of ḥadīth transmission in the city. Nevertheless, Basrah succeeded in producing robust and authoritative chains of transmission that played a crucial role in shaping the development of ḥadīth schools and the methodological foundations of Islamic legal madhhabs. This research employs a qualitative approach based on library research, utilizing primary sources in the form of classical texts alongside secondary literature to analyze the characteristics and contributions of Basrah to the Islamic ḥadīth tradition.